2008
DOI: 10.1016/j.jalz.2007.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by hypothalamic peptide proline‐rich peptide‐1 in Aβ25–35 model of Alzheimer's disease

Abstract: Systemic administration of PRP-1 possesses neuroprotective effects and can prevent the neurodegeneration in hippocampus induced by Abeta25-35. This suggests that PRP-1 could be a potential therapeutic agent for specific neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Moreover, our previous studies revealed a deficit of working and spatial memory in rats following modeling of AD by intracerebroventricular (i.c.v.) injection of Aβ 25–35, at later dates (60th, 90th days and more after Aβ 25–35 administration) [ 28 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our previous studies revealed a deficit of working and spatial memory in rats following modeling of AD by intracerebroventricular (i.c.v.) injection of Aβ 25–35, at later dates (60th, 90th days and more after Aβ 25–35 administration) [ 28 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In confirmation, the modern studies on the cellular and network levels show that synaptic inhibition cannot be assessed only as opposed to synaptic excitation and additionally serves highly specific functions in the nervous system of mammals [71]. Moreover, sustainable deepening of depression in our above-mentioned works is the result of involvement as a protective categories Galarmin or PRP-1 (proine-rich peptide), the hypothalamic neuropeptide-immunomodulator, snake venoms, parathyroid hormone (PTH), and others [50,62,63,72,73] and adrenalectomy [74][75][76] on the activity of H neurons in the amyloid model оf AD.…”
Section: Resultsmentioning
confidence: 89%
“…According to our own data, depressor response more intensively involved of both in the nonspecific (peripheral and central) and specific neurodegeneration [50][51][52]. It is supposed the advancement deepening the tetanic depression as assisting the recovery of the initial ratio of excitatory and depressor responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most study represents PRP-1, which has large spectrum of biological action on immune and nervous system, as well as universal protective effect on neurodegenerative processes [11,12]. Earlier was shown the protective effect of PRP-1 during peripheral and central neurodegeneration [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%